Exploring the Potential of ChatGPT as a Virtual Assistant for Strategic Decision-Making in Startup Businesses - Mahmudin, Tono (ADMAN: Journal of Contemporary Administration and Management, 2023)
In the current era of digital and information technology, startup businesses have emerged as primary drivers of innovation and economic growth. Startups face unique challenges, including resource constraints and the pressure to make intelligent strategic decisions to survive and thrive in a competitive market. This research aims to identify the extent to which ChatGPT can serve as an effective virtual assistant in supporting strategic decision-making in the context of startup businesses. The study conducts an extensive literature review, employing qualitative analysis methods to gain a profound understanding of the topic, covering the period from 2005 to 2023. The findings of the study indicate that exploring the potential of ChatGPT as a virtual assistant for strategic decision-making in startup businesses holds various benefits. Its ability to process information rapidly, provide deep insights, and function as an effective communication tool can offer a competitive advantage. Features such as simulation and prediction also assist business leaders in making more informed decisions. However, it is important to note that the use of ChatGPT poses ethical and data security challenges. Therefore, startup businesses are advised to adopt clear policies, ensuring compliance with ethical business norms, and maintaining data security in accordance with applicable privacy regulations.